Non-competition guaranteed value and effect on the toll road project - Zhang, Guo-Xing; Wang, Peng; Guo, Ju-E; Chai, Guorong; Liu, Peng (Transport, 2011)
A non-competition guarantee has been widely used for financing the toll road project. However, to our best knowledge, there seems to be no research about the value and incentive effect of the non-competition guarantee. In the competitive and non-competitive condition respectively, this paper constructs the models of investment value and investment threshold by adopting the option game theory and measurement approach. The results of theory derivation indicate that the non-competition guarantee plays a strong role in investment incentives by reducing investment threshold. The simulation results indicate that the non-guaranteed value increases as the expected growth rate of traffic flow increases, and decreases as volatility increases.First Published Online: 07 Jul 2011